Approaches to Studying Policy Representation. Issue 1 (February 2016) - Broockman, David E.
Abstract : Some studies of policy representation test hypotheses about the relationship between citizens' views and elites' positions on multiple issues by proceeding one issue at a time. Others summarize citizens' and elites' preferences with "ideology scores" and test hypotheses with these. I show that approach is flawed. It misinterprets citizens' ideology scores as summaries of policy preferences, but these scores actually measure ideological consistency across areas: how often citizens' ideal policies are liberal or conservative. Examples show how attending to this distinction overturns conventional wisdom: legislators appear similarly moderate as citizens, not more extreme; however, politically engaged citizens appear especially moderate.